Preliminary carbon footprint for Kansas State University - Boguski, Terrie (Kansas State University, 2009)
As concern about climate change increases, greenhouse gas inventories are being increasingly used as a measure of sustainable practices and a baseline for improvement by organizations and individuals. Carbon footprints are a common measure of the impact human activities have on the environment in terms of the amount of greenhouse gases (carbon dioxide, methane, nitrous oxide, and other gases) emitted. K-State energy usage, waste generation, water usage, and transportation data for fiscal year 2007 was used to calculate a preliminary carbon footprint for the University’s main campus; which was estimated at approximately 94,000 metric tons CO2 equivalents. Energy requirements for K-State accounted for about 92% of the total greenhouse gas emissions reported.
Keywords: Greenhouse gases; Carbon footprint; Sustainability; Energy usage; Kansas State University